Efficient synthetic approach for nanoporous adsorbents capable of pre- and post-combustion CO2 capture and selective gas separation. Issue 45 (March 2021) - Park, Jaewoo; Cho, Se Yeon; Jung, Minji; Lee, Kiyoung; Nah, Yoon-Chae; Attia, Nour F.; Oh, Hyunchul
Highlights: New synthesis approach was developed for nanoporous carbon derived from MIP. The developed porous carbons are promising for pre- and post-combustion CO2 capture The carbon adsorbent stored 22.1 mmol g −1 and 3 mmol g −1 of CO2 at 25 bar and 1 bar, Higher O-content in porous carbon attributed to remarkable selective capture of CO2 over H2, N2 and CH4 gases. The porosity and morphological properties of carbon are interesting for various industrial applications. Abstract: The level of CO2 in the atmosphere has increased rapidly due to vast quantities of fossil fuel combustion emissions, and it is accelerating global warming. Hence, pre- and post-combustion CO2 capture and storage (CCS) has become a vital necessity. Cost-effective and efficient nanoporous adsorbents for pre- and post-combustion CO2 capture were developed in this study. The highly porous and oxygen-rich carbon adsorbents were prepared in a facile one-pot process via the direct chemical activation of a molecularly imprinted polymer (MIP) and a MIP composite with activated carbon. The porous carbon adsorbent prepared from the MIP composite had a large specific surface area and specific pore volume of 3010 m 2 g −1 and 1.506 cm 3 g −1, respectively. Its bimodal pore structure contained micropores and mesopores. This nanoporous carbon adsorbent was rich in electron-dense oxygen presented in a variety of oxygen surface functional groups, which was also advantageous for CCS. These merits afforded selective CO2 adsorption and a high storage capacity under pre- and post-combustion conditions. The efficient carbon adsorbent can be stored 22.1 mmol g −1 and 3 mmol g −1 of CO2 at 25 bar and 1 bar, respectably, which was in the upper range of values reported for porous carbon. Selective CO2 capture by the carbon adsorbents was confirmed by evaluating their selectivity in CO2 /CH4, CO2 /N2, and CO2 /H2 binary gas mixtures at 298 K based on the ideal adsorbed solution theory (IAST). The most effective adsorbent had CO2 /H2 (40:60) and CO2 /N2 (50:50) selectivity of 534 and 22.6, respectively. The isosteric heat of CO2 adsorption on the porous carbon adsorbents further corroborated the selective CO2 capture.